When the Smoke Cleared : Attica Prison Poems and Journal - Tisdale, Celes, 1941-; Tisdale, Celes, 1941- (Book collections on Project MUSE., 2022)
"Following the Attica Prison uprising in September, 1971, Celes Tisdale-a poet and then professor at Buffalo State College-began leading poetry workshops with those incarcerated at Attica. Tisdale's workshop created a space of radical black creativity and solidarity, in which poets who lived through the uprising were able to turn their experiences into poetry. The poems written by Tisdale's students were published as Betcha Ain't: Poems from Attica in 1974. When the Smoke Cleared contains the entirety of Betcha Ain't, Tisdale's own poems and journal entries from the three years he taught at Attica, a previously unpublished collection of poems by Attica poets, and a critical introduction by poet Mark Nowak. In addition to the poetry, Tisdale's journal entries give readers a unique opportunity to experience what it was like to enter Attica as an educator and return week after week to discuss poetry. When the Smoke Cleared showcases these poets' achievements, desire for self-determination, and their historical role as storytellers of black life in a prison monitored exclusively by white guards and administrators"--